P111 Sleep disturbances are associated with poor neurobehavioural outcomes following traumatic brain injury: A study of military service members and veterans. (7th October 2021) - Pattinson, C; Brickell, T; Bailie, J; Hungerford, L; Lippa, S; French, L; Lange, R
Abstract: Introduction: Sleep disturbances are pervasively reported in military service members and veterans, especially following traumatic brain injury (TBI). The purpose of this study was to examine the association between sleep disturbances and neurobehavioural outcomes in a large group of U.S. military service members and veterans, with and without a history of TBI. Methods: Participants were enrolled into the Defense and Veterans Brain Injury Center/Traumatic Brain Injury Center of Excellence, 15-Year Longitudinal TBI study (N = 606). Participants self-reported sleep disturbances (PROMIS 8A) and neurobehavioral symptoms. Data were analyzed using analysis of variance with post-hoc comparisons. Four groups were analyzed separately: uncomplicated mild TBI (MTBI; n=218); complicated mild, moderate, severe, or penetrating - combined TBI (CTBI; n=118); injured controls (IC, i.e., orthopedic or soft-tissue injury without TBI; n=162); and non-injured controls (NIC; n=108). Results: Participants in the MTBI group reported the highest proportion of moderate-severe sleep disturbances (66.5%) compared to the IC (54.9%), CTBI (47.5%), and NIC groups (34.3%). Participants classified as having Poor Sleep reported significantly worse scores on almost all TBI-QOL scales compared to those classified as having Good Sleep, regardless of TBI severity or even the presence of TBI (ps<.05, Cohen's ds>.3). Discussion: This study demonstrates that sleep disturbances remain a prevalent and debilitating concern in service member and veteran populations. Regardless of group (injured or NIC), sleep disturbances were common and were associated with significantly worse neurobehavioral functioning. When assessing and treating neurobehavioural symptoms, it is important to assess sleep, especially in service member and veteran populations.